The Effectiveness of Teams Games Tournament (TGT) Based on Paired Cards on Elementary School Students' Critical Thinking Skills in Fraction Material - Anisa Diah Wardani; Karsono Karsono; Sandra Bayu Kurniawan (Sakura Digital Nusantara, 2026)
This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) learning model based on paired cards on elementary school students' critical thinking skills in fractions. This study used a quantitative approach with a quasi-experimental method and a matching-only pretest-posttest control group design. The sampling technique used was cluster random sampling, with a sample size of 78 students, consisting of 40 students in the experimental group and 38 students in the control group. Data collection was conducted using a critical thinking ability essay test containing indicators for interpretation, analysis, and evaluation. Data analysis was carried out using normality test, homogeneity test, N-gain test, and independent sample t-test assisted by SPSS Statistics 25. The results of the study showed that the paired card-based TGT model had a positive influence on the critical thinking skills of elementary school students with a significance value of 0.001 in the independent sample t-test. The experimental group achieved a higher increase in critical thinking skills (0.7048) compared to the control group (0.6090). Learning activities involving group discussions, educational games, and tournaments can increase student engagement in the mathematics learning process. This research shows that game-based cooperative learning models can be used as an alternative mathematics learning strategy to develop elementary school students' critical thinking skills. Furthermore, the use of matching cards can help create more active, collaborative, and meaningful learning. This study integrates the Teams Games Tournament (TGT) model with paired card media in elementary school mathematics learning to improve students' critical thinking skills on fraction material, which has been limitedly studied in previous studies.